Accumulating cosmopolitan and ethnic identity capital through international student mobility. Issue 7 (2nd July 2020) - Bamberger, Annette
ABSTRACT: International student mobility (ISM), particularly degree-mobility, has been primarily portrayed as the rational pursuit of economic advantage in an increasingly competitive and stratified global hierarchy of nations, academic institutions and qualifications. This focus on what has been portrayed as the pursuit of 'cosmopolitan capital', has led to other types of capital being ignored, despite evidence that cosmopolitan capital is inadequate to explain ISM in some contexts. This study looks at ethnic identity capital as a stimulus for ISM in a group of French-Jewish students in Israel and demonstrates how it combined with cosmopolitan capital helps to explain the motivation for ISM in some culturally and ethnically distinct groups.